2009
DOI: 10.1179/174313209x393564
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral vasospasm following subarachnoid hemorrhage: time for a new world of thought

Abstract: Objective Delayed cerebral vasospasm has long been recognized as an important cause of poor outcome after an otherwise successful treatment of a ruptured intracranial aneurysm, but it remains a pathophysiological enigma despite intensive research for more than half a century. Method Summarized in this review are highlights of research from North America, Europe and Asia reflecting recent advances in the understanding of delayed ischemic deficit. Result It will focus on current accepted mechanisms and on ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
286
2
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 379 publications
(296 citation statements)
references
References 73 publications
4
286
2
4
Order By: Relevance
“…Furthermore, current understanding of the development of DCI suggests a multifactorial process with microemboli, microthrombosis, macrovascular spasm, and cortical spreading depolarization all playing a part. 39 These processes may not affect the entire cerebral vasculature equally, which may contribute to the observed differences between THRT, Sxa, and TOxa.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Furthermore, current understanding of the development of DCI suggests a multifactorial process with microemboli, microthrombosis, macrovascular spasm, and cortical spreading depolarization all playing a part. 39 These processes may not affect the entire cerebral vasculature equally, which may contribute to the observed differences between THRT, Sxa, and TOxa.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…2,3 Antifibrinogen staining of cortical and hippocampal sections of saline-injected and SAH mice showed that mice with SAH had many fibrinogen-positive stained microvessels scattered throughout multiple layers of the cerebral cortex and hippocampus ( Figure 5B). In comparison, sections from eNOS KO mice showed fewer fibrinogen-stained microvessels in the brain ( Figure 5B).…”
Section: Endothelial Nitric Oxide Synthase Knockout Reduces Microthromentioning
confidence: 99%
“…Supporting this change in sentiment, clinical trials have found that the endothelin-1A receptor antagonist clazosentan significantly decreased the incidence of large-artery vasospasm but failed to improve outcome in SAH patients (8,9). Additional mechanisms that may contribute to SAH-induced DINDs include early brain injury, inflammation, cortical spreading depression, and focal cortical infarcts arising from perfusion deficiencies within the microcirculation (5,6,10,11). Perfusion deficiencies reflecting restricted blood flow through intracerebral (parenchymal) arterioles could result from microthrombi formation (12), vasoconstriction caused by extravascular blood or blood breakdown products (13,14), or impaired neurovascular coupling (15).…”
mentioning
confidence: 95%
“…For decades, delayed blood-induced vasospasm of brain surface arteries was considered the major underlying cause of SAH-induced DINDs (4,5). Recently, this paradigm has been challenged, leading to a reevaluation of the causal relationship between angiographically defined vasospasm of surface conduit arteries and SAH-induced morbidity and mortality (5)(6)(7).…”
mentioning
confidence: 99%
See 1 more Smart Citation